Effect of Transtympanic Injection of Melatonin on Cisplatin-Induced Ototoxicity - (:unkn) unknown (AVES, 2015)
OBJECTIVE: Cisplatin is a chemotherapeutic agent that is widely used in cancer treatment. Numerous side effects have been detected, one of which is ototoxicity. Melatonin, a product of the pineal gland, has a neuroendocrinoimmunological role in vertebrates. In the present study, we investigated the effects of melatonin on cisplatin-induced ototoxicity. MATERIALS AND METHODS: Twenty-four Wistar albino rats were divided into three groups. Group 1 was administered both intraperitoneal and transtympanic saline; Group 2, 12 mg/kg of intraperitoneal single-dose cisplatin and transtympanic saline; and Group 3, 12 mg/kg of intraperitoneal single-dose cisplatin and 0.1 mg/mL of transtympanic melatonin for 5 days. Before and after the procedure, distortion product otoacoustic emissions and auditory brainstem responses of all the rats were measured. At the end of the procedure, the cochleas of the rats were investigated at the microscopic level. RESULTS: Group 3 had lesser threshold shift in otoacoustic emissions and auditory brainstem responses at all frequencies than Group 2 (p<0.005). The difference was not significant between Group 1 and Group 3. On the microscopic level, more epithelial loss and less TNF staining were detected in Group 2 than in Group 3. CONCLUSION: As an antioxidant and immune modulator, melatonin is effective against cisplatin ototoxicity. Both hearing thresholds and tissue investigations supported this conclusion. Melatonin can also be used to treat cisplatin ototoxicity using transtympanic local application in lower doses.
Keywords: Melatonin; cisplatin; transtympanic; ototoxicity; cohlea; ANTIOXIDANT SYSTEM; PROTECTION; METABOLITE; RAT; GENERATION; RECEPTORS; MECHANISM; COCHLEA; CELLS